CORRELATION BETWEEN DESIGN, SERVICE AND ACTIVITY FACTOR IN CO-WORKING SPACE - Sofia Pamela; Hanson E Kusuma (Ide dan Dialog Desain Indonesia (Idealog), 2021)
The alteration of way people working caused by economy based knowledge, creativity and digital creates the spread of Co-working Space. This study aimed to identified correlation between design, services and avtivity factor in Co-working Space. Analysis result showed there are five dimension design characteristics of Co-working Space: serenity and health, physiological comfort, uniqueness, privacy and natural environment, and simplicity. Analysis result also showed six dimension of services of Co-working Space: service, restorative and work facilities, accesibility, supporting facility, complement facility, and community. Acitivity dimension of Co-working Space are educative, business, restorative, supporting, creative work, and interactive work activities. Activity dimension that has the highest mean is interactive work, restorative, and creative work activity which is has correlation with service, accessibility, and community. Those three activities also has correlation with design factor: serenity and health, physiological comfort, privacy and natural environment, and simplicity. Kata kunci : Sequential mixed-method, Karakteristik Co-working Space, Korelasi multivariat.